Pengaruh Implementasi Diabetes Self Management Education (DSME) Berbasis E-Book Terhadap Perawatan Diri Pada Pasien Dengan Ulkus Diabetikum Di Klinik Istiqamah Ulee Kareng - Riyan Mulfianda; Vanissa Salsabila; Nanda Desreza (Jurnal Ilmiah Manusia Dan Kesehatan, 2026)
Diabetes mellitus is a chronic disease that can lead to various complications, including diabetic ulcers. Maintaining the best possible care is crucial to avoid problems and complications. The purpose of the Diabetes Self-Management Education (DSME) program is to help patients become more capable of managing their condition on their own. This study aims to identify how e-book-based DSME affects diabetic ulcer patients' self-care. The study employed a quasi-experimental research design with a one-group pretest-posttest design. The population consisted of 83 patients which then, 20 patients chosen as the sample using a purposive sampling technique. The data collection instrument used a questionnaire sheet. This research was conducted at Istiqamah Ulee Kareng Clinic from May 5 to June 26, 2025. The paired t-test was used to analyze the data. The research results showed a significant increase in self-care scores after the intervention, with a p-value of 0.000 (<0.05). Based on the findings, diabetes mellitus patients with diabetic ulcers who practice good self-care are more likely to experience non-serious problems and are at a lower risk of developing long-term complications.